Benefits of using cognitive styles in the clasroom to learn a foreign language - Llanez Guzmán, Jorge Homero; Alexander López, Edwin; Moreira Cisneros, Nadia Carolina (2024)
The following bibliographical research is about Cognitive Styles. It contains objectives that are focused on the benefits that learning styles can bring to students and tutors. Also, there is a justification that show the importance of this research and who are benefited with this to have a better performance inside as well as outside the foreign language classroom. Moreover, there are arguments on how teachers can improve their techniques when teach a foreign language. Besides that, the conclusions were written to advice the readers to take advantages of theories in learning styles. The recommendations are suggested to be applied in every foreign language classroom. The methodology is included to show the readers how the steps were done to do this research. The bibliography shows the consulted resources that support the arguments presented in this bibliographical work. Finally, the appendices include the outline of this research and the questionnaire to measure the one’s learning styles.